Soil Organic Carbon and Geochemical Characteristics on Different Rocks and Their Significance for Carbon Cycles - Chen, Qiao; Zhang, Pengpeng; Hu, Ziyuan; Li, Sha; Zhang, Yongshuai; Hu, Lei; Zhou, Liangyu; Lin, Bin; Li, Xuefeng (Frontiers in Environmental Science, 2022)
Soil organic carbon (SOC) is significant for soil quality and global carbon cycles. SOC was observed to be related to soil geochemistry, and soils originating from different bedrock have different geochemical properties, but the effect of bedrock on SOC is still undefined. The soils overlying different bedrocks in Zhenxiong and Wenxin County were sampled. Specifically, the soils in the mineral horizon, which are less affected by the external environment than surface soils, are focused on to reveal the effect of bedrock on SOC. The Al/Ti, Fe/Ti and Al/Fe indicate a soil-rock successive relationship. The SOC contents in the mineral horizon are 0.19-2.74% (1.24% on average), and those in the surface horizon are 1.26-4.01% (2.63% on average). The SOC contents in the surface and mineral horizons of the same bedrock are significantly positively correlated, implying bedrock is an important factor affecting SOC. SOC in the mineral horizon is related to the first transition metal ions. Significantly positive correlations of SOC (P<0.01) with Co, Cu, Ti, V and Zn, and a positive correlation (P<0.05) with Ni were observed in the mineral horizon. Organic-transition metal complexation seems to play an important role in governing SOC in the mineral horizon. That is, the complexation maintains organic carbon stability, slows down its decomposition rate, and accumulates organic carbon. The Ca-SOC positive correlation in the mineral horizon exits because Ca also can complex with organic carbon. Co, Cu, V-SOC positive correlations (P<0.05) were also observed, but there were no significantly positive correlations (P<0.01) in the surface horizon because surface SOC had diversified sources. An SOC evolution model influenced by bedrock was forwarded. Thus, the different soil geochemistry originating from different bedrock should be noticed when SOC and global carbon cycles are discussed.